Surgical techniques in ophthalmology cataract surgery - Garg, Ashok; Alió, Jorge L; Chang, David F. (New Delhi : Jaypee-Highligts Medical Publishers, 2010)
Libro de consulta rápida para los oftalmólogos para mejorar sus habilidades quirúrgicas, cubriendo todos los tipos de técnicas quirúrgicas de cataratas
Quick reference book for ophthalmologists to sharpen their surgical skills, covering all types of cataract surgical techniques.
CONTENTS Section I: Evolution of Various Cataract Surgery Techniques and Technology Section II: Management of Complicated Cataracts and Cataract Surgery Complications Section III: Advances in Cataract Surgery Techniques and Technology
Incluye índice
Incluye índice
Keywords: CATARATAS (OFTALMOLOGIA) -- CIRUGIA; OPHTHALMOLOGIC SURGICAL PROCEDURES -- METHODS; CATARACT -- SURGERY